Hepatoblastoma with pure fetal epithelial differentiation in a 10-year-old boy: A rare case report and review of the literature. Issue 2 (January 2018) - Zhong, Shanshan; Zhao, Yang; Fan, Chuifeng
Abstract: Rationale: Hepatoblastoma is a rare malignant embryonal tumor that only accounts for approximately 1% of all pediatric cancers and mostly develops in children younger than 5 years old. Moreover, the occurrence of hepatoblastoma in adults is extremely rare. Patient concerns: Herein, we present a rare case of hepatoblastoma with pure epithelial differentiation in a 10-year-old boy.Pathological examination was performed. The tumor was 15 cm × 15 cm in size with clear margins. The cut surface was multiple nodular and grey-yellow. Histologically, the small cuboidal tumor cells were arranged in trabeculae with 2–3 cell layers. The tumor cells had eosinophilic or clear cytoplasm, formed dark and light areas, and were positive for alpha-fetoprotein, CK, CK8/18, CD10, hepatocyte, and GPC3. CD34 staining revealed that the sinusoids were lined by endothelial cells in the tumor tissues. The Ki67 index was approximately 20%. Diagnoses: Based on these findings, the case was diagnosed as hepatoblastoma with pure fetal epithelial differentiation. Interventions: The tumor was completely removed. Outcomes: No recurrence was found 3 months after the operation. Lessons: Hepatoblastoma with pure epithelial differentiation can also occur in older children. Children rarely notice and report any physical abnormality, and this may be among the primary reasons for the late diagnosis of the tumor. Annual heath checks may be beneficial in the detection of these rare tumors and improvement of patient outcomes.